Música infantil y conciencia fonológica en los niños de inicial II de la Escuela de Educación Básica Miguel Riofrio, de la ciudad de Loja, en el periodo 2022 - 2023 - Labanda Armijos, Yannina Gabriela (2023)
The present investigation determined how children's music favors phonological awareness in children of initial level II of the Miguel Riofrio basic education school, it began under a quantitative approach, with a pre-experimental design and descriptive scope, in the same way supported by analytical-synthetic and deductive-inductive methods. The instrument that allowed collecting the results was an adaptation of the PECO Test carried out by Quiroz and Suarez (2014), applied to a sample of twenty-one children from four to five years of age, being able to obtain that 71% were found at a low level, since they presented difficulties in the identification, extensions and omissions of syllables and phonemes. To solve the problem, a guide based on 25 musical activities called "Listening to and repeating songs my pronunciation is improving" was developed and applied, which was elaborated with the typology of playful, didactic and skill songs, managing to improve by 23% in the low level, passing to a medium level 48%. reaching the conclusion that the use of children's music favors the development of the acquisition of phonological awareness through the identification, deepening and omission of the different phonemic sounds. Keywords: Metalinguistic ability, oral language, musical expression, communicative strategy.